Performance strategies for musicians : how to overcome stage fright and performance anxiety and perform at your peak : using NLP and visualisation : a self-help handbook for anyone who performs : musicians, singers, actors, dancers, athletes and business managers and executives - Buswell, David (MX Publishing, 2006)
Mental wellbeing and peak performance: Musicians and mental wellbeing - Mental skills training - The performing state; Developing mental resilience: Breathing - Relaxation - Visualisation and mental rehearsal - Changing state; Practice and performance: Practice - Pre-performance - Performance.